Fund accessibility on research and output of academic staff in the University of Ibadan, Nigeria (2018)
The problem in accessing funds for research by most university academics in Nigeria has imposed serious limitations to the growth of quality research output in the country. Thus, this study investigated the influence of fund accessibility on the research output of academic staff of the University of Ibadan, Nigeria. The descriptive survey research design was adopted study. The population comprised the entire academic staff of University of Ibadan. A total of 320 academic staffs were sampled via the simple random technique. Data were collected through self-designed questionnaire and checklist Questionnaire was used to measure the extent to which fund accessibility influence research output while checklist was used to show the six years (2011-2016) trend in research funding and the of fund accessibility in the University. The collected data were analyzed using level descriptive statistics (Frequency counts and percentages) and inferential statistics (Pearson Correlation. The hypothesis was tested at 0.05 level of significance. The result showed that there is significant positive relationship between research fund accessibility and research output in the University of Ibadan. The stringent conditions attached to research grant, difficulty in the retirement process for the grant and inadequate information have made it difficult for university lecturers to access research grant This invariably has negative impact on the output of research (reduction in the research output). The study therefore recommends that university-based research grants be made readily, frequently, made and easily accessible to lecturers in the university for research output hat will enhance national social and economic development